Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, Benjamin; Köhler, Daniel; Vorderbrüggen, Julian; Troschitz, Juliane; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Production Engineering)
Abstract Recent developments in automotive and aircraft industry towards a multi-material design pose challenges for modern joining technologies due to different mechanical properties and material compositions of various materials such as composites and metals. Therefore, mechanical joining technologies like clinching are in the focus of current research activities. For multi-material joints of metals and thermoplastic composites thermally assisted clinching processes with advanced tool concepts are well developed. The material-specific properties of fibre-reinforced thermoplastics have a significant influence on the joining process and the resulting material structure in the joining zone. For this reason, it is important to investigate these influences in detail and to understand the phenomena occurring during the joining process. Additionally, this provides the basis for a validation of a numerical simulation of such joining processes. In this paper, the material structure in a joint resulting from a thermally assisted clinching process is investigated. The joining partners are an aluminium sheet and a thermoplastic composite (organo sheet). Using computed tomography enables a three-dimensional investigation that allows a detailed analysis of the phenomena in different joining stages and in the material structure of the finished joint. Consequently, this study provides a more detailed understanding of the material behavior of thermoplastic composites during thermally assisted clinching.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

In Situ Computed Tomography—Analysis of a Single-Lap Shear Test with Clinch Points - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (Materials)
As lightweight design gains more and more attention, time and cost-efficient joining methods such as clinching are becoming more popular. A clinch point’s quality is usually determined by ex situ destructive analyses such as microsectioning. However, these methods do not yield the detection of phenomena occurring during loading such as elastic deformations and cracks that close after unloading. Alternatively, in situ computed tomography (in situ CT) can be used to investigate the loading process of clinch points. In this paper, a method for in situ CT analysis of a single-lap shear test with clinched metal sheets is presented at the example of a clinched joint with two 2 mm thick aluminum sheets. Furthermore, the potential of this method to validate numerical simulations is shown. Since the sheets’ surfaces are locally in contact with each other, the interface between both aluminum sheets and therefore the exact contour of the joining partners is difficult to identify in CT analyses. To compensate for this, the application of copper varnish between the sheets is investigated. The best in situ CT results are achieved with both sheets treated. It showed that with this treatment, in situ CT is suitable to properly observe the three-dimensional deformation behavior and to identify the failure modes.
Keywords: General Materials Science

Clinching in In-situ CT – Experimental Study on Suitable Tool Materials - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (ESAFORM 2021)
In lightweight design, clinching is a cost-efficient solution as the joint is created through localized cold-forming of the joining parts. A clinch point’s quality is usually assessed using ex-situ destructive testing methods. These, however, are unable to detect phenomena immediately during the joining process. For instance, elastic deformations reverse and cracks close after unloading. In-situ methods such as the force-displacement evaluation are used to control a clinching process, though deviations in the clinch point geometry cannot be derived with this method. To overcome these limitations, the clinching process can be investigated using in-situ computed tomography (in-situ CT). However, a clinching tool made of steel would cause strong artefacts and a high attenuation in the CT measurement, reducing the significance of this method. Additionally, when joining parts of the same material, the sheet-sheet interface is hardly detectable. This work aims at identifying, firstly, tool materials that allow artefact-reduced CT measurements during clinching, and, secondly, radiopaque materials that can be applied between the joining parts to enhance the detectability of the sheet-sheet interface. Therefore, both CT-suitable tool materials and radiopaque materials are selected and experimentally investigated. In the clinching process, two aluminium sheets with radiopaque material in between are clinched in a single-step (rotationally symmetric joint without cut section). It is shown that e.g. silicon nitride is suited as tool material and a tin layer is suitable to enhance the detectability of the sheet-sheet interface.

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Historisches Lernen digital. Die neue Version der App in die Geschichte - Meyer-Hamme, Johannes; Krebs, Alexandra (Zeitschrift für Geschichtsdidaktik)

Playing as Learning and Reflecting? Theoretical Perspectives on Digital Historical Culture. London/New York, S. . - Meyer-Hamme, Johannes; Körber, Andreas; Houghton, Robert (Playing the Crusades)

Erinnerungspraktiken, Geschichtskulturen und historisches Lernen in der deutschen Migrationsgesellschaft (HiLMiG) - Meyer-Hamme, Johannes; Georgi, Viola; Lücke, Martin; Spielhaus, Riem (Migration und gesellschaftlicher Wandel – Förderlinie des Bundesministeriums für Bildung und Forschung)

Theorie – Empirie – Reflexivität. Das Paderborner Modell geschichtsdidaktischer Betreuung schulischer Langzeitpraktika von Lehramtsstudierenden im Fach Geschichte - Meyer-Hamme, Johannes; Hartung, Olaf; Krebs, Alexandra; Fastlabend-Vargas, Daniel (Geschichtsdidaktische Hochschullehre)

Poster: Enabling Comparable and Reproducible Simulations for V2X Research - Hardes, Tobias; Logan, Dalisha; Sommer, Christoph; Klingler, Florian (13th IEEE Vehicular Networking Conference (VNC 2021))
Simulations are a prime performance evaluation technique for new Vehicle to Everything (V2X) methods and approaches. However, after decades of simulation-backed research, comparability and reproducibility of simulation studies is still low. In this work, we first survey road traffic simulation parameters (that is, scenarios) employed in recent scientific publications, revealing that many publications still do not adequately describe simulation scenarios to make the results comprehensible. As just one example, over 40% of the simulations using either a Manhattan Grid or Chicago Grid do not provide information about the number of lanes. At the same time, our survey reveals that, even though employed road traffic scenarios are very use case specific, there exist many commonalities. We therefore advocate basing research on use case specific variants of a set of these common standard road traffic scenarios. We accompany this recommendation with Simple Synthetic Scenarios for Sumo (SSS4S), a simple reference implementation to generate such variants.

Towards opportunistic UAV relaying for smart cities - Hardes, Tobias; Boos, Clemens; Sommer, Christoph
With recent advances in cooperation among mobile computer systems, Unmanned Aerial Vehicles (UAVs) can be expected to be operated in large numbers and become a part of daily life for a variety of use cases. UAVs are already envi- sioned to act as mobile base stations, e.g., for situations with high node densities and strong communication requirements. However, UAVs are typically imagined to be provided specifically for this purpose. In this work, we study the effects of exploiting randomly passing UAVs at an urban intersection for the communication between vehicles on the ground. We show that a UAV, while following its pri- mary mission, can support cooperative driving vehicles in a purely opportunistic fashion by collecting periodic wireless broadcasts from vehicles and propagating all collected information periodically in an aggregated format. Using simulations, we show that such an opportunistic UAV relaying approach can lead to an improvement of approx. 6 percentage points (% points) in terms of perception of other vehicles.

Wirtschaftsregion Pader. Eine geschichtswissenschaftliche Skizze (1350-1950) - Ströhmer, Michael (Enzyklopädie Paderpedia (https://paderpedia.de/kultur-und-wirtschaftsgeschichte-der-pader))

Wirtschaftliche Aspekte des internationalen Sandsteinhandels in Nordwesteuropa: Präfabrikation - Logistik - Preise (1560-1740) - Ströhmer, Michael (Innovation in der Bauwirtschaft)

Die Wassernot des Paderborner Jesuitenkollegs - Brunnen und Wasserkünste im konfessionspolitischen Ressourcenkonflikt (1596-1629) - Ströhmer, Michael (Theologie und Glaube)

'Abgrund Mensch': Judith Kuckarts Um- und Weiterschriften der 'westfälischen Heimatdichterin' Annette von Droste-Hülshoff - Morrien, Rita (Arbeitsbuch Judith Kuckart. Erzählen - Theater - Tanz)

"Ich gehe durch andere Räume. Ich gehe durch eure Träume." - (Nicht-)Orte der Liebe in Judith Kuckarts "Kein Sturm, nur Wetter" - Morrien, Rita (Arbeitsbuch Judith Kuckart)

Die epistemische Dimension der Neuen Rechten. Von einer Kritik des Wissenschafts- und Bildungsverständnisses der Neuen Rechten zu einer Selbstkritik - Haker, Christoph; Otterspeer, Lukas (recht extrem? Dynamiken in zivilgesellschaftlichen Räumen)

Bedingte Autonomie, nicht Neutralität – „Neutrale Schulen Hamburg“ (AfD) und ihre Kritik - Haker, Christoph; Otterspeer, Lukas (Dürfen Lehrer ihre Meinung sagen? Demokratie, Bildung und der Streit über das Kontroversitätsgebot)

Against Latour – On the Questionable Foundations of Post-Critical Pedagogy - Haker, Christoph; Otterspeer, Lukas (On Education. Journal for Research and Debate)
Critique has run out of steam – this diagnosis by Bruno Latour is crucial for the “Manifesto for post-critical education” as well as for the on_education issue “The Fatique of Critique?”. With this essay, we contradict Latour's diagnosis. Latour’s polemic against critique is based firstly on a questionable diagnosis of our time and secondly on a general and programmatic critique of sociology. Against that, we bring out two main points. The first insight highlights that change is initially dependent on variations that can only arise from a negation of the existing. The second insight comes from the sociology of critique, which paradoxically sees success in the failure of critique.

Empirische Bildungsforschung als Rechtfertigung rechtspopulistischer Angst. Zur gegenwartsdiagnostischen Verwendung von Large-Scale-Assessments - Haker, Christoph; Otterspeer, Lukas (Erziehungswirklichkeiten in Zeiten von Angst und Verunsicherung)

Kritik rechtspopulistischer Gewissheiten. Für die Öffnung von Kontingenzen moderner Gesellschaftsordnungen - Haker, Christoph; Otterspeer, Lukas (Gewissheit. Beiträge und Debatten zum 3. Sektionskongress der Wissenssoziologie)

Die Beweglichkeit der Kritik: zur Wechselbeziehung von Kontextualisierung und Objektivierung im digitalen Zeitalter - Haker, Christoph; Otterspeer, Lukas (BEHEMOTH. A Journal on Civilisation)

Die Freiheit, ein*e Andere*r zu werden. Eine Bricolage zur Praxis soziologischer Theorie. - Haker, Christoph (Lebendige Theorie)

Tire Wear Reduction Based on an Extended Multibody Rear Axle Model - Schütte, Jan; Sextro, Walter (Vehicles)
To analyze the influence of suspension kinematics on tire wear, detailed simulation models are required. In this study, a non-linear, flexible multibody model of a rear axle system is built up in the simulation software MSC Adams/View. The physical model comprises the suspension kinematics, compliance, and dynamics as well as the non-linear behavior of the tire using the FTire model. FTire is chosen because it has a separate tire tread model to compute the contact pressure and friction force distribution in the tire contact patch. To build up the simulation model, a large amount of data is needed. Bushings, spring, and damper characteristics are modeled based on measurements. For the structural components (e.g., control arms), reverse engineering techniques are used. The components are 3D-scanned, reworked, and included as a modal reduced finite element (FE)-model using component mode synthesis by Craig–Bampton. Finally, the suspension model is validated by comparing the simulated kinematic and compliance characteristics to experimental results. To investigate the interaction of suspension kinematics and tire wear, straight line driving events, such as acceleration, driving with constant velocity, and deceleration, are simulated with different setups of wheel suspension kinematics. The influence of the setups on the resulting friction work between tire and road is examined, and an exemplarily calculation of tire wear based on a validated FTire tire model is carried out. The results demonstrate, on the one hand, that the chosen concept of elasto-kinematic axle leads to a relatively good match with experimental results and, on the other hand, that there are significant possibilities to reduce tire wear by adjusting the suspension kinematics.

Identification of joints for a load-adapted shape in a body in white using steady state vehicle simulations - Martin, Sven; Schütte, Jan; Bäumler, C.; Sextro, Walter; Tröster, Thomas (Forces in Mechanics)

The multiplicity of halal standards: a case study of application to slaughterhouses - Abdelrahem, Mohammed; Abdallah, Ali; Pasqualone, Antonella (Journal of Ethnic Foods)
Keywords: halal standards; halal food; slaughterhouses

High frequency limits for invariant Ruelle densities - Guillarmou, Colin; Hilgert, Joachim; Weich, Tobias (Annales Henri Lebesgue)

Algebraically Independent Generators for the Algebra of Invariant Differential Operators on SLn(R)/SOn(R) - Brennecken, Dominik; Hilgert, Joachim; Ciardo, Lorenzo (Journal of Lie Theory)

Digitalisation in the Classroom – Learning Tools - Schneider, Jennifer Nicole (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Fostering Digitisation and Industry 4.0: Education – Vocation – Industry – Future. New Opportunities and Challenges for European VET. Insight in the DigI-VET Project

Förderung von Digitalisierung und Industrie 4.0: Bildung – Beruf – Industrie – Zukunft. Neue Möglichkeiten und Herausforderungen für die europäische Berufsbildung. Einblick in das Projekt DigI-VET - Beutner, Marc; Schneider, Jennifer Nicole (Industrie 4.0- Eine Einführung in die Ideen und neuen Möglichkeiten)

Mathematik - Ein Reiseführer 2. Auflage

Higher-rank quantum-classical correspondence - Hilgert, Joachim; Weich, Tobias; Wolf, L.

Justine Favarts Rox(el)ane: Eine Relektüre von Soliman second (1761) in Text, Bild, Musik jenseits des Orientalismusparadigmas - Münzmay, Andreas (Musikwissenschaft der Vielfalt. FS Rebecca Grotjahn zum 60. Geb.)
The conventional wisdom is that Favart's 'Soliman second' is, as Larry Wolff puts it, about an "explicitly French triumph over Ottoman despotism". This may be true to a certain extent - but it misses the point. As impressive as the depiction of the 'Oriental' may have been, it is not itself the core message of this comédie, but rather only one of the means to an end, which consists of once again accompanying and authenticating Justine Favart's novel, very modern approach to realistic character representation in the best possible way. This study demonstrates this by means of a combined analysis of the theatrical levels of text, image and music. Instead of orientalism in the sense of constructing images of the exotic 'other', the textual, pictorial and musical strategies employed in this play specifically conceived for Justine Favart apply to the production of theatrical 'authenticity' and 'natural' character representation in general. The fact that the stage persona thus brought to bear, i.e. the main character Roxelane, who responds to many models from Racine to Montesquieu, is a militantly enlightened and feminist one whose 'natural' persuasiveness and force no one can ultimately resist, so that Justine Favart's Roxelane triumphantly asserts herself all along the line and establishes nothing less than a new social, gender and state order, makes the matter all the more interesting.

Philip Ording: 99 Variations on a Proof. Princeton University Press 2019 - Hilgert, Joachim (Mathematische Semesterberichte)

Georg Glaeser (Hrsg.): 77-mal Mathematik für zwischendurch – Unterhaltsame Kuriositäten und unorthodoxe Anwendungen. Springer Spektrum 2020 - Hilgert, Joachim (Mathematische Semesterberichte)

Immaterielles Kulturerbe in der Coronakrise. Gesellschaftliche Bräuche, Rituale und Feste und die Folgen von Covid-19 am Beispiel des Schützenwesens - Leineweber, Jonas (Rheinisch-Westfälische Zeitschrift für Volkskunde)

Medien der Sorge, Techniken des Selbst. Praktiken des Über-sich-selbst-Schreibens bei Christoph Schlingensief und Elfriede Jelinek - Degeling, Jasmin

Mein Handy hat schon Covid-19!‘ Digitaler Faschismus unter Bedingung der Corona-Pandemie - Degeling, Jasmin (onlinejournal kultur&geschlecht)

Medien der Sorge. Einleitung in den Schwerpunkt - Degeling, Jasmin; Haffke, Maren (Zeitschrift für Medienwissenschaft. Jg. 13, Heft 24)

Students’ learning of computational thinking in schools with different curriculum approaches including individual student characteristics - Labusch, Amelie; Eickelmann, Birgit (Proceedings of the 5th APSCE International Computational Thinking and STEM in Education Conference 2021)

Schule digital – der Länderindikator 2021. Erste Ergebnisse und Analysen im Bundesländervergleich - Lorenz, R.; Yotyodying, S.; Eickelmann, Birgit; Endberg, M.

Gelingende digitale Schulentwicklung in der Post-Pandemiezeit - Eickelmann, Birgit (SchulVerwaltung Spezial)

Gelingende digitale Schulentwicklung in der Post-Pandemiezeit - Eickelmann, Birgit (SchulVerwaltung Spezial 2021)

Schule in der digitalen Welt - Buhl, Heike M.; Bonanati, Sabrina; Eickelmann, Birgit

Charakterisierung der Abscheideeffizienz eines kombinierten Abgasreinigungsverfahrens zur simultanen Minderung von partikulären und gasförmigen Emissionen - Wortmeier, Andreas; Beimdiek, Janis

Experimentelle Untersuchung zur Abscheidung von Stäuben aus häuslichen Holzfeuerungsanlagen mittels Schüttschichtfiltration - Buff, Jasmin; Beimdiek, Janis

Kunstunterricht planen, analysieren und reflektieren. Verknüpfung von Theorie und Praxis im Fach Kunst an der Universität Paderborn am Beispiel des Praxissemesters - Waffner, Annika; Schmidt, Rebekka (Fachdidaktische Entwicklung von Lehrkräften fördern)

Student engagement in digitalen Lehr-Lern-Szenarien. Zwei Fachdisziplinen berichten - Schmidt, Rebekka; Mindt, Ilka (Hochschule auf Abstand)

Vom Binge-Eating zu Yogakursen - Prikoszovits, Matthias (Sprache im Beruf)
Keywords: General Medicine

Data Literacy: Kompetenzrahmen für Hochschulen - Bush, Annika; de Gruisbourne, Birte; Matzner, Tobias; Schulz, Christian

Digital Masculinities. YouTube, Ästhetik und männliche Körper - Hoffarth, Britta; Richter, Susanne; Wehren, Sylvia (Buzzword Digitalisierung: Kritische Perspektiven auf Digitalisierung im Kontext von Geschlecht und Vielfalt)

Hallo Schönheiten! Performances und Aushandlungen der Geschlechterordnung in der YouTube-Beauty-Community - Richter, Susanne
Keywords: {<}3

Am Herzen liegen und horchen. Eine Antwort auf das Tötungsverbot durch eine ethische Rechtfertigung eines Menschenrechts auf Leben - Kaup, Michael
Wie rechtfertigen wir die ethische Legitimität eines Tötungsverbots und wo liegen die Grenzen des Verbots? Die vorliegende Arbeit versucht eine ethische Grundlage für ein Tötungsverbot über ein Menschenrecht auf Leben zu erarbeiten: Wie lässt sich ethisch ein Menschenrecht auf Leben rechtfertigen? Die Antwort darauf mündet in der Erkenntnis, dass Menschen ein Menschenrecht auf Leben als einen Bestandteil ihrer Lebensführung und als eine Antwort auf die Frage, wie wir leben wollen, begreifen, um zu einer gesicherten ethischen Grundlage zu gelangen.
Keywords: Tötungsverbot; Recht auf Leben; Menschenrecht auf Leben

Review of: Wie die Welt in den Computer kam: Zur Entstehung digitaler Wirklichkeit [How the world came to be in the computer: On the creation of digital reality] by David Gugerli - Schmitt, Martin (Technology and Culture)

Die Digitalisierung der Kreditwirtschaft. Computereinsatz in den Sparkassen der Bundesrepublik und der DDR 1957-1991 - Schmitt, Martin

Weltweite Verfügbarkeit und digitale Langzeitarchivierung - Ried, Dennis (Mitteilungen der IMRG)

Musikalische Schrift und Digitalität. Ein Werkstattbericht - Freund, Julia; Muennich, Stefan; Ried, Dennis; Ziegler, Michelle

Lieder II

Der Liebe will ich singen. Hermann Reutters Begegnung mit dem Mittelalter - Ried, Dennis (Ritter, Tod und Teufel. Hermann Reutter und das Lied)

Werke für gemischten Chor a cappella II

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

Model based random packing optimisation for absorption processes using the hydrodynamic analogy concept - Salten, Alexander Heinrich Johannes; Kenig, Eugeny (Chemical Engineering Science)

Investigation of the pressure-throughput behavior of different faceted mixer geometries on an analytical and simulative basis - Frank, Maximilian; Hollenhorst, Viola; Schöppner, Volker (36th International Conference of the Polymer Processing - PPS 2021)

Development of a Dynamic Modeling Approach to Simulate a Segmented Distillation Column for Flexible Operation - Bruns, Bastian; Fasel, Henrik; Grünewald, Marcus; Riese, Julia (ChemEngineering)
The need for flexible process equipment has increased over the past decade in the chemical industry. However, process equipment such as distillation columns have limitations that significantly restrict flexible operation. We investigate a segmented tray column designed to allow flexible operation. The design consists of radial trays connected at the downcomer of each tray. Each segment can be operated separately, but depending on the capacity of the feed stream, additional segments can be activated or deactivated. The connection between the trays aims to transfer liquid from one stationary segment to the adjacent inactive segment, thereby reducing the time required for the start-up process. In a case study on the separation of methanol and water, we perform dynamic simulations to assess the reduction in the start-up time of inactive segments. The results confirm the advantages over standard tray designs. The segmented distillation column is a step towards improving the flexibility of separation operations.
Keywords: General Energy; General Engineering; General Chemical Engineering

Concept of a Flexible Wetted‐Wall Column for the Distillation of Specialty Chemicals - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Chemical Engineering & Technology)
Abstract The trend of increasing product diversity and decreasing production amounts led to the requirement of higher flexibility of production processes of specialty chemicals. Conventional distillation columns, mostly equipped with structured packings, lack the flexibility to handle product changeovers and throughput. Thus, a newly designed distillation column for specialty chemicals is presented. A numerical model was implemented to analyze the potential of the wetted‐wall column. The simulation of the distillation of a binary methanol/water mixture demonstrated that the wetted‐wall column can generate the desired concentration and temperature profiles. Furthermore, analyses of the pressure drop and separation efficiency with the test system chlorobenzene/ethylbenzene were conducted.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Characterization of Liquid-Phase Distribution in 3D Printed Structured Packings with an Enclosed Column Wall - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Flexibility analysis for demand-side management in large-scale chemical processes: An ethylene oxide production case study - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Indirect Demand Response Potential of Large-Scale Chemical Processes - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Dynamic Design Optimization for Flexible Process Equipment - Bruns, Bastian; Herrmann, Felix; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Efficient Production of Specialized Polymers with Highly Flexible Small‐Scale Plants - Bruns, Bastian; Becker, Tristan; Riese, Julia; Lier, Stefan; Werners, Brigitte (Chemical Engineering & Technology)
Abstract Shortened product life cycles and increased demand for specialized products lead to more challenges in efficiently satisfying customer needs. Customer demands are increasingly uncertain in terms of type, location, and volume. As a result, more flexible chemical production plants are required. Modular small‐scale plants can be installed in transportation containers and, therefore, offer the flexibility of easy relocation, enabling production close to the customer or supplier. In a mathematical optimization model, the economic benefit of small‐scale plants in the specialty chemicals market of polymer production is analyzed. Different scenarios created from the real data of a chemical company show that the use of small‐scale plants may lead to a significant reduction in total costs that is mainly due to the transportation costs of raw materials and products.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Experimentelle Untersuchungen zum Tropfenmitriss im Feedeinleitbereich von Destillationskolonnen - Fasel, Henrik; Darvishsefat, Novin; Riese, Julia; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Im Rahmen dieses Beitrags werden experimentelle Untersuchungen zur Tropfenabscheidung im Einleitbereich eines Stoffaustauschapparates für zweiphasige Strömungen vorgestellt. Dafür wurde in einem Versuchsstand im Pilotmaßstab der qualitative Tropfenmitriss für unterschiedliche Tropfenabscheider eines Stoffaustauschapparates vermessen. Die daraus resultierenden Ergebnisse werden in diesem Beitrag hinsichtlich ihrer Aussagekraft zur Vermeidung von Tropfenmitriss diskutiert und bewertet. Darüber hinaus wird ein kurzer Ausblick über simulative Arbeiten zur Bestimmung des Tropfenmitriss gegeben.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Heat transfer enhancement within internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Sheet Metal 2021)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Tribology; Sheet Metal; Simulation

"Lobe den Herren, den mächtigen König der Ehren" - Ein Lied mit Lebensbezug - Breckner, Anne (Musik als Lebensmittel: Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Conference Report: Dynamics of Tradition: Islamic Theology and Law in Relation (September 17-19, 2021, Paderborn) - Nassery, Idris; Tatari, Muna; Mustafa, Abdul Rahman

Our Energy Grids as Enabler for More Sustainability. Talk - Schlüter, Alexander

Wir müssen handeln: Jetzt! - Schlüter, Alexander; Bernabé-Moreno, Juan (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Wer grüne Energie will, muss auch koppeln und speichern - Meschede, Henning; Khripko, Diana; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities and Smart Rural Areas)

Insights into the Future Energy System in Smart Cities and Rural Areas. Talk - Schlüter, Alexander

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)

Optimization of packed bed latent heat storages filled with PCM-capsules based on super-ellipsoids - Grabo, Matti; Kuckuck, Lennart; Kenig, Eugeny

Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan Yuksel; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Feasibility study of a new static-mechanical rounding of polymer particles for selective laser sintering (Studienarbeit) - Bommidi, Karthik; Ponusamy, SathishKumar

Energie einsparen in Industrie und Gewerbe - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Mit Energieeffizienz Grundlagen legen - Hechelmann, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Der Prosumer im Zentrum des digitalen Energiesystems - Ikonnikova, Svetlana; Schlüter, Alexander; Brandner, Bernadette (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Energieeffiziente Gebäude - Emmerich-Bundel, Garance; Lindauer, Manuel; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Die smarte Kommune in Stadt und Land - Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Digitale Transformation aus der Perspektive von Kindern und Jugendlichen in Europa gestalten – das Horizon-Projekt DigiGen. PlanBD #4 Around the World - Eickelmann, Birgit; Drossel, Kerstin; Casamassima, Gianna; Labusch, Amelie (Fachmagazin für Schule in der digitalen Welt)

The younger generation’s views on how their education is preparing them for the digital age against the background of COVID-19 - Eickelmann, Birgit; Barbovschi, Monica; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, Greta Björk; Holmarsdottir, Halla Bjork; Kazani, Aggeliki; Mifsud, Louise; Parsanoglou, Dimitris; Port, Sonja; Sisask, Merike; Symeonaki, Maria; et al.

Digital diversity across Europe. Policy brief September 2021 of Working Package 2 'Mapping digital transformations across Europe' in Horizon-2020-Project DigiGen - Ayllón, Sara; Casamassima, Gianna; Drossel, Kerstin; Eickelmann, Birgit; Hyggen, Christer; Lado, Samuel; Port, Sonja; Broekstra, Nienke

Noticing im naturwissenschaftlichen Sachunterricht der Grundschule - Gövert, Andre (Sprachtheorien in der Zweit- und Fremdsprachenforschung. Eine Basis für empirisches Arbeiten zwischen Fach- und Sprachlernen.)

Digitale Prozessintegration in berufs- und wirtschaftspädagogischen Studiengängen – Überlegungen zur Professionalität und professionellen Entwicklung - Jenert, Tobias; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik – online)

Being a first-year student during COVID-19 pandemic - Büker, Ronja (Zeitschrift für Hochschulentwicklung)

Anderssein als Ressource: Habitus und Habitusreflexion in der Lehrer*innenbildung - Jenert, Tobias (PraxisForschungLehrer*innenbildung)
Lehrer*innen können dazu beitragen, dass bestehende soziale Ungleichheiten verstärkt oder auch abgebaut werden. Eine wichtige Rolle spielen dabei der sogenannte Habitus der Lehrer*innen und dessen (Nicht-)Passung zur sozialen Herkunft der Schüler*innen. In diesem Text stelle ich die Frage, wie angehende Lehrer*innen im Studium unterstützt werden können, die Bedeutung eigener habitueller Prägungen für das professionelle Handeln als Lehrperson zu reflektieren. Ganz besonders befasse ich mich mit der Rolle der Lehrer*innenbildner*innen bei der Förderung von solchen habitusreflexiven Kompetenzen. Hier spielen das Selbst der Hochschullehrenden und die bildungsbiographischen Erfahrungen, die auf dem Weg in die Hochschule gemacht wurden, eine wichtige Rolle.

Digitale Prozessintegration in der beruflichen Lehrer*innenbildung – Praxisnahe Einblicke in die Entwicklung des wirtschaftspädagogischen Studienangebots an der Universität Paderborn - Sänger, Niklas

Einblicke in die curriculare Entwicklung des wirtschaftspädagogischen Studienangebots mit Hilfe der Fallstudiendidaktik - Sänger, Niklas

Soziale Netzwerke als Treiber und Qualitätsmerkmal einer lehrbezogenen Hochschulentwicklung - Sänger, Niklas; Jenert, Tobias